Assessing the effectiveness of flying ad hoc networks for international border surveillance - Fayez Al Fayez; Mohammad Hammoudeh; Bamidele Adebisi; Khalid Nazim Abdul Sattar (International Journal of Distributed Sensor Networks)
International border security operations are diverse and include tasks to facilitate the legitimate movement of goods, thwart crime, maintain safety around borders and safeguard natural resources. All these operations are vital and enduring; however, three operations are currently of exceptional concern to countries around the world: counterterrorism, illegal drug control and illegal migration. The usage of flying ad hoc networks promises new ways for both military and civilian applications, such as border surveillance and remote sensing. Many systems were developed to assist border authorities with more effective surveillance and reliable decision-making support. Such systems vary in terms of the used technology, accuracy, types of events that can be detected and monitoring continuity. This article investigates the technical capabilities of existing and emerging surveillance technologies used for international border monitoring applications. It describes the effectiveness of these systems along with the technological infrastructure required for their implementation. Particular attention has been given to identifying the strengths and weaknesses of these systems and their ability to meet current and future challenges. Our analysis shows that flying ad hoc networks can be used to deliver a rapidly deployable, self-configurable, flexible and relatively small operating cost network for border surveillance.